The Effectiveness of Digital Marketing as a Promotional Media Paddy Agro-Tourism in The Village of Market Transfer - Adelina Lubis; Nurul Wardani Lubis; Indah Apriliya; Julistia Wardhani (Institute of Computer Science (IOCS), 2022)
Pasar Melintang Village has a rice field location developed into one of the agro-tourism areas in the Deli Serdang Regency. Where currently, the existence of this location is only known to the local village community and requires further development. The aims of this study are to 1) Analyze the influence of personal characteristics on visiting interest and 2) Analyze the effectiveness of digital marketing in moderating the relationship between personal characteristics and visiting interest. Independent variables are personal characteristics and digital marketing as a moderating variable. The population in this study is the people of the Lubuk Pakam District. The sampling technique used is purposive sampling with the following criteria: 1) Respondents have come to the village rice field tourism location, 2) Minimum age is 17 years, 3) Minimum education is high school equivalent. When collecting data, the team was able to get sixty-three respondents who met the criteria. The analysis technique used was Moderated Regression Analysis. The results of this study are that personal characteristics have no significant effect on the interest of visiting tourists. However, digital marketing can effectively moderate the relationship between personal characteristics and interest in visiting.